(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
Entomological material was collected for the study of coccinellides (Coleoptera, Coccinellidae) of the Karshi oasis in 2018-2021. Analysis of the material revealed the distribution of 8 types of coccinellides.